Occurrence and reassortment of avian influenza A (H7N9) viruses derived from coinfected birds in China - Liu, W; Fan, H; Raghwani, J; Lam, T; Li, J; Pybus, O; Yao, H; Wo, Y; Liu, K; An, X; Pei, G; Li, H; et al. (American Society for Microbiology, 2014)
Over the course of two waves of infection, H7N9 avian influenza A virus has caused 436 human infections and claimed 170 lives in China as of July 2014. To investigate the prevalence and genetic diversity of H7N9, we surveyed avian influenza viruses in poultry in Jiangsu province within the outbreak epicenter. We found frequent occurrence of H7N9/H9N2 coinfection in chickens. Molecular clock phylogenetic analysis confirms coinfection by H7N9/H9N2 viruses and also reveals that the identity of the H7N9 outbreak lineage is confounded by ongoing reassortment between outbreak viruses and diverse H9N2 viruses in domestic birds. Experimental inoculation of a coinfected sample in cell culture yielded two reassortant H7N9 strains with polymerase segments from the original H9N2 strain. Ongoing reassortment between the H7N9 outbreak lineage and diverse H9N2 viruses may generate new strains with the potential to infect humans, highlighting the need for continued viral surveillance in poultry and humans.We found frequent occurrence of H7N9/H9N2 coinfection in chickens. The H7N9 outbreak lineage is confounded by ongoing reassortment between H7N9 and H9N2 viruses. The importance of H9N2 viruses as the source of novel avian influenza virus infections in humans requires continuous attention.